THE IMPLEMENTATION OF AUTOMATIC SPRAYER IN FARMING GROUP IN KUTA DAME VILLAGE - Waluyo, Bakti Dwi; Suryanto, Eko Dodi; Dalimunthe, Amirhud; Restu, Restu (Universitas Negeri Medan, 2020)
The majority of people in Kuta Dame Village work as farmers. Several outreaches have been carried out to develop the agricultural sector in Kuta Dame village. However, some of the extension services rarely touched on effective technology to support agriculture in Kuta Dame village. One of the technologies that need to be developed by the Kuta Dame village farmer group in supporting agriculture is an automatic sprayer. This development is necessary because most farmers are still using the carrying type sprayer with a manual pump (diaphragm pump). The sprayer's diaphragm pump pressure produces a relatively low spray pressure, especially when the operator is tired of moving the pump lever. As a result, the spraying performance is not perfect, making the spray grains not smooth and not reaching the leaf surface evenly. A community service program was implemented to implement automatic sprayers for farmers in Kuta Dame village. This community service program aims to carry out the planning process and use of an electric sprayer appropriately to increase spraying fertilizers and pesticides on crops. Implementing this community service activity starts from planning activities, implementing academic counseling, implementing the practice, handing over an electric sprayer, monitoring, and satisfaction analysis.